2009
DOI: 10.1074/jbc.m808331200
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Regulates Matrix Metalloproteinase-2 in Ovarian Cancer by Modulating cAMP-response Element-binding Protein Activity

Abstract: Tissue transglutaminase 2 (TG2) is overexpressed in epithelial ovarian cancer (EOC) and promotes intraperitoneal metastasis. How TG2 facilitates the spread of EOC is unknown. Here, we show that TG2 regulates the expression and function of matrix metalloproteinase-2 (MMP-2), a critical mediator of tissue invasiveness. TG2 knockdown down-regulates MMP-2 protein and mRNA expression in SKOV3, IGROV-1, MDA-MB-436, and PC-3 cancer cells. TG2 knockdown or inhibition of TG2 activity using KCC009 decreases MMP-2 gelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 38 publications
7
48
1
Order By: Relevance
“…This was associated with a reduced activity of the MMP promoters, which was dependent on putative CREB-or CRE-binding sites. Modulation of MMP-2 and -9 promoter activity by CREB has also been shown in different cell systems (49)(50)(51). Furthermore, the transcriptional upregulation of MMP-2 and -9 by CREB not only increased their invasion potential in vitro and in vivo, but also enhanced angiogenesis in vivo (52), which was not addressed in the present study.…”
contrasting
confidence: 48%
“…This was associated with a reduced activity of the MMP promoters, which was dependent on putative CREB-or CRE-binding sites. Modulation of MMP-2 and -9 promoter activity by CREB has also been shown in different cell systems (49)(50)(51). Furthermore, the transcriptional upregulation of MMP-2 and -9 by CREB not only increased their invasion potential in vitro and in vivo, but also enhanced angiogenesis in vivo (52), which was not addressed in the present study.…”
contrasting
confidence: 48%
“…Suppression of MMP-9 expression with siRNA substantially inhibited cell migration/invasion, suggesting that MMP-9 is one of the major MMPs that contribute to acquired TRAIL resistance-associated migration/ invasion. Although regulated by TGM2 in certain cancer cell types, other MMPs such as MMP-2 are unlikely involved in migration in the lung cancer cells with acquired TRAIL resistance (36). This observation suggests that the mechanisms of TGM2 in cancer cell migration/invasion are cell type-specific or that the functioning mechanism of TGM2 in acquired TRAIL resistance-associated migration/invasion is distinct to that in cancer cells with primary apoptosis resistance.…”
Section: Discussionmentioning
confidence: 59%
“…It has been shown that TGM2 promotes cell growth, survival, and motility or invasion (38,39). Although increased TGM2 expression in cancer cells has been linked to increased drug resistance, metastasis, and poor patient survival (36,37,40), to our knowledge, this is the first report showing that TGM2 is overexpressed when acquired TRAIL resistance arises with the association of increased cell migration and invasion. Although the regulation of TGM2 expression is complex, EGFR-mediated cell signaling is implicated in up-regulation of TGM2 expression in cancer cells (32).…”
Section: Discussionmentioning
confidence: 79%
“…This was dependent on CREB because mutations of the three putative CREB-binding sites in the MMP-9 promoter resulted in a significantly decreased activity, while a deletion of the single CRE site decreased the MMP-2 promoter activity by 20%. Although the binding of CREB to the MMP-2 and MMP-9 promoter had already been shown in different studies (43,44), this effect has not yet been linked to RAS transformation. These data are in line with reports demonstrating that CREB protein elimination decreased the activities of MMP in NSCLC (45) and melanoma (42).…”
Section: Discussionmentioning
confidence: 99%